IMPLEMENTATION OF BIOLOGY LEARNING IMPLEMENTATION IN THE INDEPENDENT CURRICULUM FOR TEACHERS AND GRADE X STUDENTS AT MAN 1 SOUTHWEST ACEH - Tahir, Muhammad (Jurnal Review Pendidikan dan Pengajaran, 2025)
The independent curriculum was formalized by the Minister of Education and Culture which stipulates that there are several things that must be prepared before learning after that implementing independent curriculum learning by differentiating learning and assessment. The formulation of the problem in this study is “How is the application of an independent curriculum in biology learning by teachers and grade X students at MAN 1 Southwest Aceh and what are the obstacles experienced during the biology learning process on an independent curriculum by teachers and grade X students at MAN 1 Southwest Aceh”. The purpose of this study was to describe the implementation of biology learning in the independent curriculum by teachers and students of class X MAN 1 Southwest Aceh and describe the obstacles experienced in the biology learning process in the independent curriculum by teachers and students of class X MAN 1 Southwest Aceh. The method used in this research is a qualitative approach with descriptive research type with data collection techniques, namely observation carried out by observing learning, interview techniques by interviewing teachers and students, questionnaires conducted by giving research instruments to teachers and students, and documentation in the form of storage data collection during observation, questionnaire filling and during interviews. The data analysis technique used is qualitative data analysis technique. The results of this study indicate that teachers in class X biology subjects at MAN 1 Southwest Aceh have implemented the independent curriculum for the 2023/2024 school year, this is indicated by the existence of teachers carrying out lesson planning using the Project Based Learning model and including Learning Outcomes (CP), involving students in compiling the Flow of Learning Objectives and the existence of teaching modules. The obstacles experienced during the learning process are that not all students provide a reciprocal response in the implementation of the project, the teacher is still not effective in determining the hours for the implementation of the planned project and what challenges the teacher is the implementation of learning assessment. The implementation of teachers and students in biology learning in the independent curriculum has been carried out well.